2015
DOI: 10.12968/bjcn.2015.20.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Optimising concordance with compression hosiery in the community setting

Abstract: Compression hosiery is used to help prevent leg ulcer recurrence by controlling venous backflow and the build-up of lower-limb oedema. The therapy is effective, but only if it is worn consistently by patients. In order to promote concordance with ongoing management, it is important that practitioners are aware of the options available in terms of design, structure, colour and size of compression. It is also vital for practitioners to consider a range of strategies to help patients apply and remove the hosiery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…3,7,36,52,53 A systematic literature review shows that every form of properly employed compression favorably influences the process of venous ulceration healing, and it is difficult to determine which method is the most effective. 25,34,54 In the research carried out by Szewczyk among 112 people suffering from venous ulcers, the healing dynamics of ulceration treated with 2-and 4-layer compression system was comparable. 4 In another study conducted in an ulceration treatment clinic on a group of 46 patients with venous ulcers, the authors demonstrated a similar effectiveness of the 2and 4-layer system as well as compression stockings.…”
Section: Discussionmentioning
confidence: 96%
“…3,7,36,52,53 A systematic literature review shows that every form of properly employed compression favorably influences the process of venous ulceration healing, and it is difficult to determine which method is the most effective. 25,34,54 In the research carried out by Szewczyk among 112 people suffering from venous ulcers, the healing dynamics of ulceration treated with 2-and 4-layer compression system was comparable. 4 In another study conducted in an ulceration treatment clinic on a group of 46 patients with venous ulcers, the authors demonstrated a similar effectiveness of the 2and 4-layer system as well as compression stockings.…”
Section: Discussionmentioning
confidence: 96%
“…Discussion Compliance with compression is the key to achieving wound healing in patients with VLUs but compliance rate remains low. Consequently, effort needs to be made by healthcare professionals (HCPs) to improve compliance and therapeutic relationships through holistic patient assessment that addresses their experiences and values their individualism, health beliefs, lifestyle and social networks 4,5 . Further studies to identify intervention strategies that can increase their compliance are required.…”
Section: Resultsmentioning
confidence: 99%
“…Thematic analysis of the findings in Table 1 was undertaken, and five determinant factors contributing to patients' noncompliance to compression therapy were identified and discussed. Pain [1][2][3][4]7,8,11,13,14,[16][17][18] and discomfort [1][2][3][4]6,7,9,13,[15][16][17][18][19] were key factors that emerged, followed by psychosocial issues [1][2][3][4][7][8][9]11,[13][14][15][16][17][18] , knowledge deficit 1,3,7,8,11,13,14,16,17 , physical limitations 1,…”
Section: Determinant Factors Contributing To Non-compliancementioning
confidence: 99%
See 2 more Smart Citations